Third Hankel determinant for reciprocal of bounded turning function has a positive real part of order alpha - VENKATESWARLU, Bolineni; RANI, Nekkanti (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
The objective of this paper is to obtain an upper bound to the third Hankel determinant denoted by |H3(1)| for certain subclass of univalent functions, using Toeplitz determinants. Mathematics Subject Classification (2010): 30C45, 30C50.